Agro-morphological, micropropagation and cellular behavior studies of sainfoin (Onobrychis Viciifolia Scop. Syn. Onobrychis sativa l.) / Sadegh Mohajer - Mohajer, Sadegh (2013)

(untitled)
In order to study the variations and relationship among morphological and quality traits, 12 populations (accessions) of Sainfoin (Onobrychis viciifolia Scop. Syn. Onobrychis sativa L.), were assessed under sward growth condition using split plot design with three replications during a two year period. Based on the above experiments, three best varieties of Sainfoin were selected for further investigation, i.e Golpaygan-181, Orumieh-1763 and Gorgan-1601. To explore the potential for in vitro rapid regeneration of Sainfoin (Onobrychis viciifolia), different concentrations of 6-Benzylaminopurine (BAP), 1-Naphthaleneacetic acid (NAA) and BAP combined with Indole-3-butyric acid (IBA) were evaluated for their effects on the induction of somatic embryos from leaf, stem and root explants. Different explants were cultured on MS medium supplemented with various concentrations (0, 0.5, 1, 1.5, 2, 2.5 and 3 mg L-1) of each kind of hormone. Callus induction percentage, fresh weight, color and texture of the callus were assessed after 11 and 22 days of culture to compare the effect of the different concentrations. The optimum medium for the proliferation of embryogenic callus from leaf and root explants was MS supplemented with 2.5 mg L-1 BAP and 0.5 mg L-1 NAA. For the first time, synthetic seed of Sainfoin was created and established. An encapsulation protocol to obtain adventitious shoots from synthetic seeds of Sainfoin was achieved from leaf and stem derived somatic embryogenic callus containing torpedo and cotyledonary stages which were coated in different concentrations of sodium alginate either in MS medium or soil. Initiated adventitious buds developed into rooting following culture on full and half strength MS medium supplemented with BAP, NAA, IBA and IAA with various concentrations (0.25, 0.5, 1 and 2 mg L-1) of each hormone. v The developed plantlets were successfully adapted to the natural conditions after several steps of acclimatization with 98% of survival rate. It can be suggested that by using Scanning Electron Microscope (SEM), comparison of intact (in vivo) and in vitro leaf tissues could be evaluated clearly. In the current study, it was found that different resistance strategies of Onobrychis viciifolia could be assessed based on stomata, epicuticular waxes, convex cell, trichomes and calcium oxalate crystals function. Plant propagation can also be achieved from somatic embrygenic callus. In this respect, various explants were induced and two types of callus including embrygenic (E) and nonembrygenic (NE) were obtained. Cytological studies of embryonic and non-embryogenic callus as well as root meristem cells of in vitro and in vivo grown plants as the main tissues of this species were carried out. Mitotic behavior was generally regular for all growth conditions, but some irregularities such as cytomixis, binucleated cells and bridge chromosomes were occasionally observed, especially in non-embryogenic callus. In addition, callus and seeds of Sainfoin were exposed to five levels of UV-B radiation (312 nm) to study the influence of increasing UV-B intensity on pigment study, seed quality, cytological and phytochemical processes of both intact and in vitro growth conditions. Assessment of results from callus as well as on different tissues of in vitro and in vivo grown Sainfoin showed that flavonoid and phenolic compounds were increased compared to the control cells, at 40% and 60% intensity, respectively. In order to study seed quality as one of the explants sources, seven parameters were assessed to investigate the effects of UV-B radiation, such as percentage of crude protein (CP), percentage of crude fiber (CF), percentage of ash, percentage of acid detergent fiber (ADF), percentage of dry matter digestibility (DMD), percentage of water-soluble carbohydrates (WSC) and percentage of neutral detergent fiber (NDF). According to vi obtained results, atomic spectroscopy analysis confirmed that concentrations of trace metals (Mn and Cu) and macro-nutrients (Ca, P and N) changed after UV radiation treatment. HPLC analysis conducted on radiated seed extracts showed the presence of key alkaloids, namely Berberine and Sanguinarine. In vitro mutagenesis techniques were also applied to investigate the effects of gamma irradiation at 0, 30, 60, 90 and 120 Gy on mitotic behavior, pigment study, biological and phytochemical processes and also seed quality of Sainfoin (Onobrychis viciifolia). Ultimately, changes in seed viability due to environmental conditions (cold stress and relative humidity) are crucial factors to preserve seed germination ability in equatorial zones. In this regard, the effect of relative humidity (RH) and cold storage on seed viability, quality and element content of three varieties of Onobrychis viciifolia were investigated. Mean relative humidity (RH) of 83-84% hastened the loss of seed viability during 6 months, while stored seeds at -20 ºC exerted only a minimal deteriorative effect on percentage of the seed germination and vigour index. Generally, this research consisted of four main aspects respectively, which are; 1. Morphological study and genetic diversity to choose the best varieties and assess in important intact plant traits, 2. Tissue culture of superior varieties for callus induction and micropropagation, 3. Cytological study of callus, in vitro and in vivo grown plants to assess the prior study based on the cellular behavior, and to detect any occurrence of somaclonal variation in Sainfoin. 4. To create, modify and develop novel ideas, some studies were designed such as synthetic seeds according to obtained results of the last three studies and new breeding prospect of Onobrychis viciifolia. Seed as one of the explant resources was chosen either for direct study of quality and element content or for indirect investigation of different parameters in mature plants under both in vivo and in vitro growth conditions.